Post-genomic era in agriculture and veterinary science: successful and proposed application of genetic targeting technologies - Mazloum, Ali; Karagyaur, Maxim; Chernyshev, Roman; van Schalkwyk, Antoinette; Jun, Ma; Qiang, Fu; Sprygin, Alexander (Frontiers in Veterinary Science, 2023)
Gene editing tools have become an indispensable part of research into the fundamental aspects of cell biology. With a vast body of literature having been generated based on next generation sequencing technologies, keeping track of this ever-growing body of information remains challenging. This necessitates the translation of genomic data into tangible applications. In order to address this objective, the generated Next Generation Sequencing (NGS) data forms the basis for targeted genome editing strategies, employing known enzymes of various cellular machinery, in generating organisms with specifically selected phenotypes. This review focuses primarily on CRISPR/Cas9 technology in the context of its advantages over Zinc finger proteins (ZNF) and Transcription activator-like effector nucleases (TALEN) and meganucleases mutagenesis strategies, for use in agricultural and veterinary applications. This review will describe the application of CRISPR/Cas9 in creating modified organisms with custom-made properties, without the undesired non-targeted effects associated with virus vector vaccines and bioactive molecules produced in bacterial systems. Examples of the successful and unsuccessful applications of this technology to plants, animals and microorganisms are provided, as well as an in-depth look into possible future trends and applications in vaccine development, disease resistance and enhanced phenotypic traits will be discussed.